Sustainable neighbourhood elements model (SNES model) - Ahmad Shakri, Md Rajuna (2011)
In recent decade, the sustainability was emphasised to become the foundation of planning and design of building structures and infrastructures. Therefore, the land use development for neighbourhood construction should be protected from being overused and devastated. The main concern of this study is to introduce the Sustainable Neighbourhood Elements (SNEs) into the current practice of sustainable neighbourhood planning and design in Malaysia. The elements of sustainable neighbourhood were identified and analysed for them to be applied into the current planning and design system. Issues pertaining Malaysia's sustainable neighbourhood were discussed. A preliminary set of decision making model and evaluation framework has been developed based on the SNEs which urban designers can manipulate to suit the current need. It must be stressed that the model are preliminary and their role is to act as a catalyst in adapting new ideas into the planning and urban design process.